1890 Vt. Acts & Resolves 83, No. 82, § 19, pt. 15 - (:unkn) unknown (My University, 1890)
Granted the village the power to restrain the use of firecrackers, rockets, squibs, and toy pistols in the village
Keywords: DISCHARGE